2013
DOI: 10.2337/db12-1479
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Human Pancreas From Foregut to Endocrine Commitment

Abstract: Knowledge of human pancreas development underpins our interpretation and exploitation of human pluripotent stem cell (PSC) differentiation toward a β-cell fate. However, almost no information exists on the early events of human pancreatic specification in the distal foregut, bud formation, and early development. Here, we have studied the expression profiles of key lineage-specific markers to understand differentiation and morphogenetic events during human pancreas development. The notochord was adjacent to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
407
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(447 citation statements)
references
References 43 publications
20
407
1
4
Order By: Relevance
“…These data are supported by reports that the expression of Ngn3 and Hes1 is mutually exclusive in the developing pancreas (27,35), as is the expression of Sox9 and Ngn3 at the endocrine progenitor stage (46,(103)(104)(105). Furthermore, Sox9 occupancy regions on the Ngn3 gene promoter have been identified (104,106).…”
Section: Nsc Biology Suggests the Involvement Of Noncanonical Signalisupporting
confidence: 72%
“…These data are supported by reports that the expression of Ngn3 and Hes1 is mutually exclusive in the developing pancreas (27,35), as is the expression of Sox9 and Ngn3 at the endocrine progenitor stage (46,(103)(104)(105). Furthermore, Sox9 occupancy regions on the Ngn3 gene promoter have been identified (104,106).…”
Section: Nsc Biology Suggests the Involvement Of Noncanonical Signalisupporting
confidence: 72%
“…It has been shown that the development of the dorsal pancreas bud from the foregut endoderm is affected by the adjacent notochord (35,36), as well as the signals coming from the dorsal aorta and other vessels (37,38). In human embryos, the dorsal foregut epithelium, which is a single line in the 4-12 somite period, was found to be close to the notochord (39). In mice and chicks, it has been shown that the dorsal aorta induces pancreatic development, particularly the insulin expression of the dorsal pancreatic endoderm (37).…”
Section: Pancreas Developmentmentioning
confidence: 99%
“…The border of the pancreatic areas and the formation and growth of the pancreatic bud are similar within the ventral and dorsal foregut in both the species. Following these events, separate cell lines are seen to become different (39,42).…”
Section: Pancreas Developmentmentioning
confidence: 99%
“…It is well known that once the mesenchymal cells proliferate between aortic ECs and the foregut endoderm, the aorta is pulled out from the subjacent gut (compare Figure 2 with Figure 3) [20,55] . This fact implies that the subjacent foregut starts receiving signals from the mesenchyme and that a gradient can be formed with diluted signals from aortic ECs.…”
Section: Signals From Pancreatic Mesenchyme Toward Exocrine Pancreasmentioning
confidence: 99%
“…The pancreas originates from ventral and dorsal buds formed in the foregut at 8.5 d post-coitum (d.p.c) of gestation in mice and Carnegie stage 12 (CS12) in humans [54][55][56] . The cells that composed these buds express transcription factors such as PDX-1 which is a key regulator of pancreas development [57][58][59] .…”
Section: Endothelium Role In the Pancreatic Nichementioning
confidence: 99%